Male lower urinary tract symptoms associated with overactive bladder - Drake, Marcus J. (Canadian Medical Association, 2012)
Lower urinary tract symptoms (LUTS) associated with overactive bladder (OAB) are more likely to respond to antimuscarinic therapy than to alpha blockade. As such, initial treatment of men with storage symptoms should incorporate an antimuscarinic agent. For men who are truly refractory to current pharmacotherapies, there is emerging evidence to support the use of botulinum toxin A.